A method for preparing antistatic and wear-resistant protective film material

By introducing a polyaniline-grafted polyester antistatic agent into the PET polyester film material, the problem of poor antistatic properties of PET materials is solved, its wear resistance and tensile properties are improved, and the mechanical properties of PET are maintained.

CN119286020BActive Publication Date: 2025-04-22HEBEI SULAMEDER PLASTIC FILMS MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411822890.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-22
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The antistatic properties of PET polyester film materials are poor, and their wear resistance and tensile properties also need to be improved.

Method used

By coupling the bromine polyester with 4-aminophenyl boric acid pinenol ester, an anirine polyester with a side chain containing aniline groups was obtained, and a oxidative polymerization reaction was used to obtain a polyaniline grafted polyester antistatic agent, and finally melt blended with PET resin and made a film to form an antistatic and wear-resistant protective film material.

Benefits of technology

The antistatic properties, wear resistance and tensile properties of the PET protective film are improved, and the wear amount is reduced. The similar compatibility between the antistatic agent and PET does not affect the mechanical properties of PET.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present invention relates to the field of PET technology, and discloses a method for preparing an antistatic wear-resistant protective film material, wherein 100 parts by weight of polyethylene terephthalate and 5-15 parts by weight of a sparse polyaniline grafted polyester antistatic agent are co-extruded and stretched to obtain an antistatic wear-resistant protective film material. The antistatic agent of the present invention contains a main chain of ethylene terephthalate copolyester molecules, has good similar compatibility with PET polyester, does not affect the mechanical properties of the PET protective film, and simultaneously the side chain contains a large amount of polyaniline conductive polymers, which are uniformly dispersed in a PET matrix, significantly reduce the surface resistivity of the PET protective film, improve antistatic performance, and has good practical applications in aspects such as vehicle body protective films, display screen protective films, and LED lamps.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PET, in particular to a method for preparing an antistatic and wear-resistant protective film material. Background Art

[0002] PET polyethylene terephthalate has excellent mechanical properties and good heat resistance. It can be made into plastics, alloys, films and other materials, and is widely used in the fields of automobile protective films, packaging films, etc. The resistivity of traditional PET materials is relatively large, and the antistatic performance is poor, which limits the practical application of PET materials. Antistatic agents such as sulfonate anionic antistatic agents, quaternary ammonium salt cationic antistatic agents, and carbon black inorganic antistatic agents are added to PET. Polyaniline is a new type of conductive polymer that can be used as an antistatic agent to improve the conductivity and antistatic properties of polymer materials. Patent CN108623976B discloses an antistatic light-shielding PET film and a preparation method thereof. Polyethylene terephthalate is grafted with styrene sulfonic acid, polyaniline is coated with nano copper and other raw materials, and the obtained PET film has good antistatic properties. However, the patent does not improve the tensile properties and wear resistance of the PET film, and the compatibility of polyaniline with traditional PET is poor, which will affect the mechanical properties of the PET material. Summary of the invention

[0003] The invention solves the problem of poor anti-static performance of PET polyester film materials and simultaneously improves the wear resistance and tensile performance of the polyester film materials.

[0004] The technical solution of the present invention is: a method for preparing an antistatic and wear-resistant protective film material:

[0005] (1) Add solvent, terephthaloyl chloride, 5-bromoisophthaloyl chloride (CAS registration number: 57863-69-1), ethylene glycol and pyridine to a flask in an ice bath, stir and react at 20-30°C for 36-48 hours, add methanol for precipitation, filter, wash with water and ethanol in turn, and dry to obtain a bromo polyester.

[0006] (2) Add N,N-dimethylformamide and bromo polyester to a flask, stir and add 4-aminophenylboronic acid pinacol ester, bis(triphenylphosphine)palladium dichloride and auxiliary agent, introduce nitrogen, heat to 110-120°C, stir and react for 48-72h, cool and add methanol for precipitation, filter and wash with water, ethyl acetate and ethanol in turn, and dry to obtain aniline polyester. The reaction formula is as follows:

[0007] .

[0008] (3) Ball-mill the aniline-based polyester and sieve it, add it to a flask, add isopropanol, stir, add hydrochloric acid solution and aniline, dropwise add an aqueous solution containing ammonium persulfate in an ice bath, stir and react for 5-8 hours, filter, wash with water and ethanol in turn, and dry to obtain a polyaniline grafted polyester antistatic agent. The reaction formula is as follows:

[0009] .

[0010] (4) Add 100 parts by weight of polyethylene terephthalate, 5-15 parts by weight of polyaniline grafted polyester antistatic agent, and 0.3-0.5 parts by weight of antioxidant into an extruder, set the temperature of the sixth section of the extruder at 240-275°C, and the screw speed at 200-300 r / min, and extrude the mixture; then stretch it through a biaxial stretching machine, with a longitudinal stretching temperature of 110-120°C and a stretching ratio of 3-4 times; and a transverse stretching temperature of 125-135°C and a stretching ratio of 3-4 times, to obtain an antistatic and wear-resistant protective film material.

[0011] Preferably, the molar amounts of terephthaloyl chloride, 5-bromoisophthaloyl chloride and pyridine are 60-85%, 15-40% and 240-280% of the molar amount of ethylene glycol, respectively.

[0012] Preferably, the solvent in (1) is N,N-dimethylformamide, chloroform or 1,1,2,2-tetrachloroethane.

[0013] Preferably, the mass of 4-aminophenylboronic acid pinacol ester, bis(triphenylphosphine)palladium dichloride and the auxiliary agent in (2) is 22-60%, 0.9-2.6% and 14-45% of the mass of the bromo polyester.

[0014] Preferably, the auxiliary agent is sodium carbonate or potassium carbonate.

[0015] Preferably, the mass of aniline and ammonium persulfate in (3) is 800-2000% and 1700-4200% of the mass of the aniline-based polyester, respectively.

[0016] Technical effect: The present invention polymerizes terephthaloyl chloride, 5-bromoisophthaloyl chloride and ethylene glycol, and then couples with 4-aminophenylboronic acid pinacol ester to obtain an aniline polyester containing an aniline group in the side chain, and uses the amino group as the polymerization site to initiate an oxidative polymerization reaction of the aniline monomer to obtain a polyaniline grafted polyester antistatic agent. Finally, it is melt-blended with PET resin and film-formed to obtain an antistatic and wear-resistant protective film material.

[0017] The antistatic agent of the invention contains the main chain of ethylene terephthalate copolyester molecules, has good similar compatibility with PET polyester, and will not affect the mechanical properties of the PET protective film. Meanwhile, the side chain of the antistatic agent contains polyaniline molecular chains, forming a unique sparse structure, forming a stable physical cross-linking network with the PET molecular chains, improving the interaction between polyaniline and PET, and being beneficial to improving the tensile strength and elongation at break of PET, reducing the amount of abrasion, and improving the wear resistance.

[0018] The side chain of the antistatic agent of the invention contains a large amount of polyaniline conductive polymer, which is uniformly dispersed in the PET matrix, significantly reduces the surface resistivity of the PET protective film, improves the antistatic performance, and has good practical applications in vehicle body protective films, display screen protective films, LED lamps, etc. DETAILED DESCRIPTION

[0019] For ease of understanding of the present invention, preferred embodiments of the present invention are provided below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0020] Embodiment 1:

[0021] (1) In an ice bath, add 300 mL of N,N-dimethylformamide solvent, 85 mmol of terephthaloyl chloride, 15 mmol of 5-bromoisophthaloyl chloride, 100 mmol of ethylene glycol, and 260 mmol of pyridine to a flask, stir and react at 25°C for 36 hours, add methanol for precipitation, filter, wash with water and ethanol in turn, and dry to obtain a bromo polyester.

[0022] (2) Add 200 mL of N,N-dimethylformamide and 5 g of bromo polyester into a flask, stir and add 1.1 g of 4-aminophenylboronic acid pinacol ester, 0.045 g of bis(triphenylphosphine)palladium dichloride and 0.7 g of auxiliary sodium carbonate, introduce nitrogen, heat to 110°C, stir and react for 60 hours, cool and add methanol for precipitation, filter and wash with water, ethyl acetate and ethanol in turn, and dry to obtain aniline polyester.

[0023] (3) Ball-mill 2 g of aniline-based polyester and sieve it, add it to a flask, add 50 mL of isopropanol, stir, add 400 mL of 2 mol / L hydrochloric acid solution and 16 g of aniline, add 500 mL of an aqueous solution containing 40 g of ammonium persulfate dropwise in an ice bath, stir and react for 5 h, filter, wash with water and ethanol in turn, and dry to obtain a polyaniline grafted polyester antistatic agent.

[0024] (4) Add 1 kg of polyethylene terephthalate, 50 g of polyaniline grafted polyester antistatic agent, and 4 g of antioxidant 1076 into an extruder. The temperatures of the six sections of the extruder are 240°C, 255°C, 265°C, 270°C, 275°C, and 275°C. The screw speed is 200 r / min, and the mixture is extruded. Then, the mixture is stretched by a biaxial stretching machine. The longitudinal stretching temperature is 110°C, and the stretching ratio is 3.5 times. The transverse stretching temperature is 130°C, and the stretching ratio is 3.5 times. Thus, an antistatic and wear-resistant protective film material is obtained.

[0025] Embodiment 2:

[0026] (1) In an ice bath, add 300 mL of 1,1,2,2-tetrachloroethane solvent, 78 mmol of terephthaloyl chloride, 22 mmol of 5-bromoisophthaloyl chloride, 100 mmol of ethylene glycol, and 240 mmol of pyridine to a flask, stir and react at 30°C for 36 h, add methanol for precipitation, filter, wash with water and ethanol in turn, and dry to obtain a bromo polyester.

[0027] (2) Add 250 mL of N,N-dimethylformamide and 5 g of bromo polyester into a flask, stir and add 1.6 g of 4-aminophenylboronic acid pinacol ester, 0.073 g of bis(triphenylphosphine)palladium dichloride and 1.14 g of auxiliary potassium carbonate, introduce nitrogen, heat to 110°C, stir and react for 72 hours, cool and add methanol for precipitation, filter and wash with water, ethyl acetate and ethanol in turn, and dry to obtain aniline polyester.

[0028] (3) Ball-mill 2 g of aniline-based polyester and sieve it, add it to a flask, add 50 mL of isopropanol, stir, add 600 mL of 2 mol / L hydrochloric acid solution and 23 g of aniline, add 700 mL of an aqueous solution containing 54 g of ammonium persulfate dropwise in an ice bath, stir and react for 8 h, filter, wash with water and ethanol in turn, and dry to obtain a polyaniline grafted polyester antistatic agent.

[0029] (4) Add 1 kg of polyethylene terephthalate, 80 g of polyaniline grafted polyester antistatic agent and 3 g of antioxidant 1076 into an extruder. The six-stage temperatures of the extruder are 240°C, 255°C, 265°C, 270°C, 275°C and 275°C. The screw speed is 300 r / min and the mixture is extruded. Then, the mixture is stretched by a biaxial stretching machine. The longitudinal stretching temperature is 120°C and the stretching ratio is 4 times. The transverse stretching temperature is 130°C and the stretching ratio is 4 times. Thus, an antistatic and wear-resistant protective film material is obtained.

[0030] Embodiment 3:

[0031] (1) In an ice bath, add 400 mL of chloroform solvent, 70 mmol of terephthaloyl chloride, 30 mmol of 5-bromoisophthaloyl chloride, 100 mmol of ethylene glycol, and 280 mmol of pyridine to a flask, stir and react at 30°C for 36 hours, add methanol for precipitation, filter, wash with water and ethanol in turn, and dry to obtain a bromo polyester.

[0032] (2) Add 300 mL of N,N-dimethylformamide and 5 g of bromo polyester into a flask, stir and add 2.2 g of 4-aminophenylboronic acid pinacol ester, 0.104 g of bis(triphenylphosphine)palladium dichloride and 1.57 g of auxiliary sodium carbonate, introduce nitrogen, heat to 120°C, stir and react for 48 hours, cool and add methanol for precipitation, filter and wash with water, ethyl acetate and ethanol in turn, and dry to obtain aniline polyester.

[0033] (3) Ball-mill 2 g of aniline-based polyester and sieve it, add it to a flask, add 80 mL of isopropanol, stir, add 750 mL of 2 mol / L hydrochloric acid solution and 32 g of aniline, add 1000 mL of an aqueous solution containing 70 g of ammonium persulfate dropwise in an ice bath, stir and react for 8 h, filter, wash with water and ethanol in turn, and dry to obtain a polyaniline grafted polyester antistatic agent.

[0034] (4) Add 1 kg of polyethylene terephthalate, 120 g of polyaniline grafted polyester antistatic agent, and 5 g of antioxidant 1076 into an extruder. The six-stage temperatures of the extruder are 240°C, 255°C, 265°C, 270°C, 275°C, and 275°C. The screw speed is 300 r / min, and the mixture is extruded. Then, the mixture is stretched by a biaxial stretching machine. The longitudinal stretching temperature is 110°C and the stretching ratio is 3 times. The transverse stretching temperature is 135°C and the stretching ratio is 3 times. Thus, an antistatic and wear-resistant protective film material is obtained.

[0035] Embodiment 4:

[0036] (1) In an ice bath, add 400 mL of N,N-dimethylformamide, 60 mmol of terephthaloyl chloride, 40 mmol of 5-bromoisophthaloyl chloride, 100 mmol of ethylene glycol, and 240 mmol of pyridine to a flask, stir and react at 20°C for 48 h, add methanol for precipitation, filter, wash with water and ethanol in turn, and dry to obtain a bromo polyester.

[0037] (2) Add 300 mL of N,N-dimethylformamide and 5 g of bromo polyester into a flask, stir, then add 3 g of 4-aminophenylboronic acid pinacol ester, 0.13 g of bis(triphenylphosphine)palladium dichloride, and 2.25 g of auxiliary potassium carbonate, introduce nitrogen, heat to 120°C, stir and react for 60 hours, cool, add methanol for precipitation, filter, wash with water, ethyl acetate, and ethanol in turn, and dry to obtain aniline polyester.

[0038] (3) Ball-mill 2 g of aniline-based polyester and sieve it, add it to a flask, add 80 mL of isopropanol, stir, add 900 mL of 2 mol / L hydrochloric acid solution and 40 g of aniline, add 1200 mL of an aqueous solution containing 84 g of ammonium persulfate dropwise in an ice bath, stir and react for 8 h, filter, wash with water and ethanol in turn, and dry to obtain a polyaniline grafted polyester antistatic agent.

[0039] (4) Add 1 kg of polyethylene terephthalate, 150 g of polyaniline grafted polyester antistatic agent and 3 g of antioxidant 1076 into an extruder. The six-stage temperatures of the extruder are 240°C, 255°C, 265°C, 270°C, 275°C and 275°C. The screw speed is 200 r / min and the mixture is extruded. Then, the mixture is stretched by a biaxial stretching machine. The longitudinal stretching temperature is 110°C and the stretching ratio is 3 times. The transverse stretching temperature is 125°C and the stretching ratio is 3 times. Thus, an antistatic and wear-resistant protective film material is obtained.

[0040] Comparative Example 1:

[0041] (1) Add 1 kg of polyethylene terephthalate and 4 g of antioxidant 1076 into an extruder. The six-stage temperatures of the extruder are 240°C, 255°C, 265°C, 270°C, 275°C, and 275°C. The screw speed is 200 r / min, and the mixture is extruded. Then, the mixture is stretched by a biaxial stretching machine. The longitudinal stretching temperature is 110°C and the stretching ratio is 3.5 times. The transverse stretching temperature is 130°C and the stretching ratio is 3.5 times. A protective film material is obtained.

[0042] Comparative Example 2:

[0043] (1) Add 1 kg of polyethylene terephthalate, 50 g of aniline polyester and 4 g of antioxidant 1076 into an extruder. The six-stage temperatures of the extruder are 240°C, 255°C, 265°C, 270°C, 275°C and 275°C, and the screw speed is 200 r / min. Blend and extrude; then stretch through a biaxial stretching machine, with a longitudinal stretching temperature of 110°C and a stretching ratio of 3.5 times; and a transverse stretching temperature of 130°C and a stretching ratio of 3.5 times to obtain a protective film material.

[0044] Comparative Example 3:

[0045] (1) Add 400 mL of 2 mol / L hydrochloric acid solution and 16 g of aniline into a flask, add 500 mL of an aqueous solution containing 40 g of ammonium persulfate dropwise in an ice bath, stir and react for 5 h, filter, wash with water and ethanol in turn, and dry to obtain a polyaniline antistatic agent.

[0046] (2) Add 1 kg of polyethylene terephthalate, 50 g of polyaniline antistatic agent, and 4 g of antioxidant 1076 into an extruder. The six-stage temperatures of the extruder are 240°C, 255°C, 265°C, 270°C, 275°C, and 275°C. The screw speed is 200 r / min, and the mixture is extruded. Then, the mixture is stretched by a biaxial stretching machine. The longitudinal stretching temperature is 110°C, and the stretching ratio is 3.5 times. The transverse stretching temperature is 130°C, and the stretching ratio is 3.5 times. A protective film material is obtained.

[0047] The tensile properties of the protective film material are tested according to GB / T 13542.2-2021 standard. The tensile rate is 100 mm / min.

[0048] Table 1 Tensile properties of membrane materials

[0049]

[0050] The friction performance was tested according to ASTM G99-04 standard.

[0051] Refer to the method of GB / T 1410-2006 to test the surface resistivity of the protective film material, and the test voltage is 500V.

[0052] Table 2 Wear resistance and antistatic properties of protective film materials

[0053]

[0054] It can be seen from Table 1 and Table 2 that the PET protective film material of Comparative Example 1 has low transverse and longitudinal tensile strength and elongation at break, poor mechanical properties, large abrasion loss and surface resistivity, and poor wear resistance and antistatic properties.

[0055] The PET protective film material of Examples 1-4 is added with a sparse polyaniline grafted polyester antistatic agent, the main chain of the antistatic agent is ethylene terephthalate copolyester, which has good similar compatibility with PET polyester and will not affect the mechanical properties of the PET protective film. At the same time, the side chain of the antistatic agent contains a polyaniline molecular chain, forming a unique sparse structure, forming a stable physical cross-linking network with the PET molecular chain, improving the interaction between polyaniline and PET, and being beneficial to improving the tensile strength and elongation at break of PET, reducing the amount of abrasion, and improving the wear resistance. At the same time, polyaniline, as a conductive polymer and an antistatic agent, can reduce the surface resistivity of the PET protective film and improve the antistatic performance.

[0056] Compared with Example 1, aniline polyester is added to the PET of Comparative Example 2. The two have good compatibility and have almost no effect on the mechanical properties of the PET protective film. The tensile strength, elongation at break and abrasion of the protective film are very similar to those of Comparative Example 1. However, aniline polyester does not contain polyaniline molecular chains with a sparse structure, resulting in a significantly higher volume resistivity of the PET protective film than that of Example 1, poor antistatic properties, and slightly lower tensile strength and elongation at break than those of Example 1.

[0057] Comparative Example 3 only adds polyaniline as an antistatic agent and does not contain polyester molecular chains, and has poor compatibility with PET, which affects the mechanical properties of the PET protective film, resulting in a large decrease in tensile strength and elongation at break, increased abrasion, and poor wear resistance.

[0058] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing an antistatic and wear-resistant protective film material, characterized in that: The preparation method is: (1) Add a solvent, terephthaloyl chloride, 5-bromoisophthaloyl chloride, ethylene glycol, and pyridine to a flask in an ice bath, stir to react, add methanol to precipitate, filter, wash, and dry to obtain a bromo polyester; (2) Add N,N-dimethylformamide and bromo polyester to a flask, stir, add 4-aminophenylboronic acid pinacol ester, bis(triphenylphosphine)palladium dichloride, and an auxiliary agent, introduce nitrogen, stir to react, add methanol to precipitate, filter, wash, and dry to obtain anilino polyester; (3) Ball-mill the aniline-based polyester and sieve it, add it into a flask, add isopropanol, stir, add hydrochloric acid solution and aniline, add dropwise an aqueous solution containing ammonium persulfate in an ice bath, filter after reaction, wash, and dry to obtain a polyaniline-grafted polyester antistatic agent; (4) Add 100 parts by weight of polyethylene terephthalate, 5-15 parts by weight of polyaniline grafted polyester antistatic agent, and 0.3-0.5 parts by weight of antioxidant into an extruder, blend and extrude, and then stretch through a biaxial stretching machine to obtain an antistatic and wear-resistant protective film material; The molar amounts of terephthaloyl chloride, 5-bromoisophthaloyl chloride and pyridine in (1) are 60-85%, 15-40% and 240-280% of the molar amount of ethylene glycol respectively; The mass of 4-aminophenylboronic acid pinacol ester, bis(triphenylphosphine)palladium dichloride and auxiliary agent in (2) is 22-60%, 0.9-2.6% and 14-45% of the mass of bromo polyester; The masses of aniline and ammonium persulfate in (3) are 800-2000% and 1700-4200% of the mass of the aniline-based polyester, respectively.

2. The method for preparing the antistatic wear-resistant protective film material according to claim 1, characterized in that: The reaction temperature in (1) is 20-30°C and the reaction time is 36-48h.

3. The method for preparing the antistatic wear-resistant protective film material according to claim 1, characterized in that: The solvent in (1) is N,N-dimethylformamide, chloroform or 1,1,2,2-tetrachloroethane.

4. The method for preparing the antistatic wear-resistant protective film material according to claim 1, characterized in that: The auxiliary agent is sodium carbonate or potassium carbonate.

5. The method for preparing the antistatic wear-resistant protective film material according to claim 1, characterized in that: The reaction temperature in (2) is 110-120°C and the reaction time is 48-72h.

6. The method for preparing the antistatic wear-resistant protective film material according to claim 1, characterized in that: The reaction time in (3) is 5-8 hours.

7. The method for preparing the antistatic wear-resistant protective film material according to claim 1, characterized in that: The temperature of the sixth section of the extruder in (4) is 240-275°C, and the screw speed is 200-300 r / min; the longitudinal stretching temperature of the biaxial stretching machine is 110-120°C, and the stretching ratio is 3-4 times; the transverse stretching temperature is 125-135°C, and the stretching ratio is 3-4 times.

Citation Information

Patent Citations

  • An antistatic light-shielding PET film and its preparation method

    CN108623976B

  • Water-resistant wear-resistant antistatic polyester film and preparation method thereof

    CN113336991A

  • Modified PET film material and preparation method thereof

    CN117903579A